2020
DOI: 10.1111/tbed.13886
|View full text |Cite
|
Sign up to set email alerts
|

The role of sampling by cotton swab in the molecular diagnosis of cutaneous leishmaniasis

Abstract: Widespread in the old world and the new, the leishmaniasis is a group of diseases caused by protozoan parasites from more than 20 Leishmania species (Desjeux, 1996), transmitted to humans by the bites of the infected female phlebotomine sand fly. Cutaneous leishmaniasis (CL) is the most common form of the disease and causes skin lesions-mainly ulcers-on exposed parts of the body, leaving lifelong scars and serious disability or stigma. About 95% of CL cases occur in the Americas, the Mediterranean Basin, the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…DNA may be acquired from a vast range of clinical specimens, and each approach has varying advantages in terms of diagnostic sensitivity and specificity, ease of collection, transport and storage and invasiveness. For CL, the punch biopsy is the most commonly performed diagnostic procedure, but less invasive sampling can be achieved by using skin scrapings, fine needle aspiration and swabs, although sensitivity is sacrificed with these methods [ 131 134 ]. For post-kala-azar dermal leishmaniasis, split skin smears and skin biopsies are most commonly used [ 135 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…DNA may be acquired from a vast range of clinical specimens, and each approach has varying advantages in terms of diagnostic sensitivity and specificity, ease of collection, transport and storage and invasiveness. For CL, the punch biopsy is the most commonly performed diagnostic procedure, but less invasive sampling can be achieved by using skin scrapings, fine needle aspiration and swabs, although sensitivity is sacrificed with these methods [ 131 134 ]. For post-kala-azar dermal leishmaniasis, split skin smears and skin biopsies are most commonly used [ 135 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…Adams and co-workers found that a lesional swab processed with Qiagen ® DNA extraction was the most efficient, sensitive, and specific recovery method for Leishmania DNA, when compared with aspirate samples, which were also more painful and more complicated to obtain [ 61 ]. This approach has now been further validated in several other studies that support the use of cotton swabs for the non-invasive collection of diagnostic material for subsequent PCR analysis [ 62 65 ]. Although rubbing over the lesion with cotton swabs potentially yields a low parasitic load, several studies have indicated that the choice of the subsequent nucleic acid extraction and amplification method influences the results obtained with cotton swab collection [ 61 , 63 ].…”
Section: Laboratory Diagnosismentioning
confidence: 98%
“…Although rubbing over the lesion with cotton swabs potentially yields a low parasitic load, several studies have indicated that the choice of the subsequent nucleic acid extraction and amplification method influences the results obtained with cotton swab collection [ 61 , 63 ]. Moreover, the minimally invasive cotton swab collection method could be useful for children or in cases where the cosmetic outcome is of importance, such as in patients with facial lesions [ 65 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…The accuracy of swabbing, another patient-friendly technique, was assessed in an endemic area of Morocco. The molecular detection of Leishmania from swab samples was less sensitive than the traditional techniques, and this could be due to the low parasitic load obtained from swab samples [ 75 ]. Moreover, to assess Leishmania infection, patients urine was also found to be useful as a diagnostic tool in the surveillance of CL and VL [ 76 ].…”
Section: Discussionmentioning
confidence: 99%